The Mastery of Basic Multiplication and Division Skills and Its Impact on Students' Mathematics Achievement - Kristesia, Elda; Suriansyah, Ahmad; Harsono, Arta Mulya Budi; Putra, Eka Cahya Sari; Mubarok, Mubarok (Balai Publikasi Indonesia, 2025)
This study examines the impact of mastering basic multiplication and division concepts on the mathematics achievement of elementary school students. Using a qualitative approach in the form of a case study, the research was conducted at SDN Teluk Dalam 12 through observations and interviews involving 5th-grade students. The findings indicate that students faced significant difficulties in understanding and applying these fundamental operations, leading them to rely on multiplication tables and resulting in low academic performance. This study highlights the importance of innovative and interactive teaching strategies to enhance students' understanding and support their cognitive development. Collaboration among teachers, parents, and the school environment is crucial in overcoming these challenges and improving mathematics learning outcomes